Multipoint laser Doppler vibrometry with single detector : principles, implementations, and signal analyses - Fu, Yu (2011)
A 20-point laser Doppler vibrometer with single photodetector is presented for noncontact dynamic measurement. A 5 × 4 beam array with various frequency shifts is generated by a 1:55 μm distributed feedback laser and four acousto-optic devices, and illuminating different points on vibrating objects. The reflected beams are coupled into a single-mode fiber by a pigtailed collimator and interfere with a reference beam. The signal output from a high-speed photodetector is amplified and then digitized by a high-speed analog-to-digital converter with a sampling rate of 1 gigasample per second (1GS/s). Several methods are introduced to avoid the cross talk among different frequencies and extract the vibration information of 20 points from a one-dimensional signal. Two signal processing algorithms based on Fourier transform and windowed Fourier transform are illustrated to extract the vibration signals at different points. The experimental results are compared with that from a commercial single-point laser vibrometer. The results show simultaneous vibration measurement can be realized on multiple points using a single laser source and a single photodetector.